Post-Operative Restlessness During Recovery Period Following General Anaesthesia - Ali, Md Rashid; Adam, Shamim; Khan, KR; Imran, Zahir Al (KYAMC Journal, 2017)
Background: Smooth induction and smooth maintenance, smooth reversal and quite recovery is a key word in general anaesthesia. All anaesthetist desires that his patients wake-up smoothly & quietly. However the matter is not easy at all. Anaesthetist often faces a bitter experiences & awk.ward situation during recovery from anaesthesia. Objective: To detect the degree & frequency of restlessness in various types of patients of different age & sex groups and in different types of operations. Methodology & Materials : Our study was carried out in North Bengal Medical College Hospital, Sirajgonj, in between July/2014 & December/2014. 60 (sixty) patients were chosen of different age & sex group and of different types of operation for this perpous. Results: Our study shows that the patients of E.N.T. surgery & the patients of Paediatric surgery, were most vulnerable & responded badly, during reversal and in the post operative ward. Among others a few of them developed restlessness due to some other cause. The children were more prone to develop restlessness than the adults. The Orthopaedic surgery patients also responded badly during recovery period. Conclusion: Special attention should given to this matter as it is really a hazardous situation to all; (i.e. anaesthetist, surgeon, O.T. Sister). An adequate pre-medication,smooth induction, quiet maintenance, smooth reversal & a suitable post operative analgesic is absolutely necessary. Pre anesthetic visit & close rapport with the patient is also essential to overcome this situation. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 645-648